An Infected Sac in the Mandible – A Case Report. - Harshada Ragunathan1 , Sankar Narayanan R2 , Nalini Aswath3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Dentigerous cyst is the second most common cyst. It is usually associated with the impacted thirdmolars, canines and premolars. Clinically they present with asymptomatic swelling, bony expansion andradiographically they are well defined and the larger cyst leads to destruction of bone later leading topathological fracture. They are chances where this cyst can be misdiagnosed when seen only clinicallywithan infected tooth. Radiographic investigation is the gold standard in diagnosing the lesion and its extentfor treatment planning. The protein content of the cyst fluid also helps in the diagnosis. Here is a case wherethe patient complained of a decayed tooth along with swelling in the left side of face and how the diagnosischanged after proper history and radiographic investigation.